Diphtheria in Metro Manila, the Philippines 2006–2017: A Clinical, Molecular, and Spatial Characterization. (11th March 2020) - Saito, Nobuo; Dimapilis, Virginia O; Fujii, Hiroshi; Suzuki, Motoi; Telan, Elizabeth Freda O; Umipig, Dorcas Valencia; Solante, Rontgene M; Dimapilis, Alexis Q; De Guzman, Ferdinand; Salva, Eumelia P; Nakayama, Fumihito; Toda, Kohei; et al.
Abstract: Background: Diphtheria is a vaccine-preventable disease that persists as a global health problem. An understanding of the pattern of disease is lacking in low- and middle-income countries such as the Philippines. Methods: We conducted a retrospective review of the clinical, microbiological, and epidemiological features of patients admitted with a clinical diagnosis of diphtheria to an infectious disease referral hospital in Metro Manila, the Philippines, between 2006 and 2017. Cases were mapped and the distribution was compared with population density. Corynebacterium diphtheriae isolates from between 2015 and 2017 were examined by multilocus sequence typing (MLST). Results: We studied 267 patients (range:12−54 cases/year) admitted between 2006 and 2017. The case fatality rate (CFR) was 43.8% (95% confidence interval, 37.8−50.0%). A higher number of cases and CFR was observed among children <10 years. Mortality was associated with a delayed admission to hospital and a lack of diphtheria antitoxin. Between 2015 and 2017 there were 42 laboratory-confirmed cases. We identified 6 multilocus sequence types (STs). ST-302 was the most common (17/34, 48.6%), followed by ST67 (7/34, 20%) and ST458 (5/34, 14%). Case mapping showed a wide distribution of diphtheria patients in Metro Manila. Higher case numbers were found in densely populated areas but with no apparent clustering of ST types. Conclusions: Our analysis indicates that diphtheria remains endemic in Metro Manila and that the infection is frequently fatal in young children. Improved vaccine coverage and a sustainable supply of diphtheria antitoxin should be prioritized. Abstract : We studied 267 patients with diphtheria hospitalized in Metro Manila over 11 years. Case fatality rate was 43.8%, higher in children <10 years, those with delayed treatment, or who did not receive diphtheria antitoxin. Cases were widely distributed without clustering.